Future Drivers of Growth in Rwanda : Innovation, Integration, Agglomeration, and Competition - World Bank Group (Washington, DC: World Bank, 2018)
A strong and widely acknowledged record of economic success—including a three-and-ahalf- fold increase in per capita income since 1994—places Rwanda among the world’s fastest-growing economies. Traumatic memories of the 1994 genocide are gradually fading, as associations begin to take a more positive form—of a nation on the rise, powered by human resilience, a sense of common purpose, and a purposeful government. Past successes and a sense of frailty have fueled aspirations for a secure, prosperous, and modern future. Sustaining high rates of economic growth is at the heart of these ambitions. Recent formulations of the nation’s Vision 2050 set a target of achieving upper-middleincome status by 2035 and high-income status by 2050. Future Drivers of Growth in Rwanda: Innovation, Integration, Agglomeration, and Competition, a joint undertaking by experts from Rwanda and the World Bank Group, evaluates the country’s possibilities and options in this endeavor. The report identifies four essential drivers of growth—innovation, integration, agglomeration, and competition—and reforms in six priority areas: human capital development, export dynamism and regional integration, well-managed urbanization, competitive domestic enterprises, agricultural modernization, and capable and accountable public institutions.